A study of ethical perspective towards tax evasion in Sri Lanka - Wijerathna, A.G.H.S.K.; Perera, H.A.P.L. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
Tax evasion is a major problem in developing countries like Sri Lanka. Tax revenue is one of the main sources of government revenue. Government has to face difficulties of funding the government projects and paying for government expenditure when tax payers do not pay or under pay taxes. This study is aimed at identifying the ethical perspective of Sri Lankans towards tax evasion. Further, this study is also aimed at analyzing tax evasion based on several demographic characteristics and identifying the strongest arguments that are in favor and against of tax evasion from an ethical point of view. Data was collected from 50 tax payers and 50 non-tax payers through a questionnaire and analyzed. Based on the analysis conducted, it was identified that the strongest argument which is in against of tax evasion is, “tax evasion is ethical if everyone is doing it”. Further, the strongest argument which is in favor of tax evasion is, “tax evasion is ethical even if a large portion of money collected is spent on projects that do benefit the tax payer”. The findings if this study would be useful for the government in order to take actions to improve the tax collection from Sri Lankans.
Keywords: Ethics; Sri Lanka; Tax Evasion